Epistemic beliefs in science, socio-economic status, and mathematics and science test results in lower secondary education: a multilevel perspective. Issue 1 (2nd January 2023) - Rozgonjuk, Dmitri; Konstabel, Kenn; Barker, Kayla; Rannikmäe, Miia; Täht, Karin
Abstract: The role of epistemic beliefs in science (EBS) and socio-economic status (SES) on mathematics and science test results on both student- and school-level data was investigated via a secondary analysis of Estonian Programme for International Student Assessment (PISA) 2015 survey data. The effective sample comprised 3991 students (52% girls, 48% boys) from 81 schools. Complementing bivariate correlation analysis, two-level regression models were computed where mathematics and science test scores were predicted from student- and school-level EBS as well as SES. Mathematics and science test scores had a medium-sized correlation with both EBS as well as SES on the student-level data. These correlations were larger on the school-level data. Multilevel analyses showed that both higher mathematics and science scores were predicted by male gender, higher student-level SES and EBS, and higher school-level SES. Higher school-level EBS significantly predicted better science test scores, but this was not the case with mathematics.